1999
DOI: 10.1007/s000180050398
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to the treatment of small-cell lung cancer

Abstract: Small-cell lung cancer (SCLC) is characterized by its initial responsiveness to chemotherapy and the appearance of early metastases. Although combination chemotherapy, in some instances together with radiation, has improved the prognosis of this disease, in most patients SCLC ultimately recurs in a drug-resistant form. Several new strategies for the eradication of SCLC are being explored at the preclinical level. The identification of selective target molecules on the surface of SCLC cells, together with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…Most of the remaining cases are classified as small-cell lung cancer (SCLC). 42,43 Zangemeister-Wittke et al 44 reported that the most prominent advances in the treatment of SCLC, provided by preclinical and clinical studies during the last decade, that require further investigation are; (i) recent improvements in chemo-and radiation therapy; (ii) advances in targeting cell surface antigens, autocrine growth factors and their receptors, and modulators of drug resistance; (iii) advances in targeting the molecular basis of increased proliferation and apoptosis deficiency of tumor cells, such as the use of bcl-2antisense oligodeoxynucleotides or the replacement of inactivated or lost tumor suppressor genes. Miller et al 45 showed that local therapy, either surgery or radiation alone, had no significant impact on the survival of SCLC patients.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the remaining cases are classified as small-cell lung cancer (SCLC). 42,43 Zangemeister-Wittke et al 44 reported that the most prominent advances in the treatment of SCLC, provided by preclinical and clinical studies during the last decade, that require further investigation are; (i) recent improvements in chemo-and radiation therapy; (ii) advances in targeting cell surface antigens, autocrine growth factors and their receptors, and modulators of drug resistance; (iii) advances in targeting the molecular basis of increased proliferation and apoptosis deficiency of tumor cells, such as the use of bcl-2antisense oligodeoxynucleotides or the replacement of inactivated or lost tumor suppressor genes. Miller et al 45 showed that local therapy, either surgery or radiation alone, had no significant impact on the survival of SCLC patients.…”
Section: Introductionmentioning
confidence: 98%
“…Present treatments of SCLC generally involve high-dose combination chemotherapy with or without radiation therapy (1–11). Although there is a high initial response rate to these treatments, and long-term survival in up to 10% of all cases (8, 9, 11), average life expectancy is increased by only 8–15 months. While about 80% of these newly diagnosed SCLC patients respond to chemotherapy, remission generally lasts only 3–6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Present treatments for patients with SCLC generally involve them having high-dose combination chemotherapy with or without radiation therapy. 1 6 Although there is a high initial response rate to these treatments, and long-term survival in up to 10% of all cases, 1 , 6 10 average life expectancy is increased by only 8–15 months. While about 80% of these newly diagnosed SCLC patients respond to chemotherapy, remission generally lasts only 3–6 months.…”
Section: Introductionmentioning
confidence: 99%